Aniseikonia: A 21st Century Look. Issue 2 (3rd April 2019) - Furr, Bruce A.
ABSTRACT: Purpose : Aniseikonia, an appreciation of image size differences between the eyes, can produce symptoms in patients, ranging from headaches to loss of fusion. The purpose of this research was to take a 21st century look at aniseikonia. Methods : Kellogg Eye Center patient records were evaluated for measurable aniseikonia in patients tested with the Aniseikonia Helper, a tablet-based application. Anaglyph slides for the synoptophore were developed to test the limits of induced aniseikonia on stereopsis and fusion. A survey was developed to determine how frequently members of the American Association of Certified Orthoptists (AACO) examine and treat patients with aniseikonia.Results : The prevalence of measurable aniseikonia in this cohort was 7.8%. Moderate amounts of induced aniseikonia, 4% induced image size disparity, disrupt fusion and can cause a loss of stereopsis. Eighty percent of responding AACO members see patients with aniseikonia and among those, 25% see them on a monthly basis. Treatment options, other than wearing contact lenses, are limited to occlusion or fogging techniques. Conclusions : Aniseikonia remains a frequent complaint among patients. The ophthalmologic community needs to use the best methods for measuring aniseikonia and to develop better methods for treating aniseikonia.